Ten Lectures on the Cultural Legacy of Dream of the Red Chamber
XV, 201 p. 3 illus., 2 illus. in color.
Keywords: This book offers a profound exploration of the classic Chinese novel Dream of the Red Chamber, recognized as a masterpiece of traditional Chinese literature. Developed from a series of lectures at the Shanghai Library, the text features insights from ten prominent scholars, including Wang Meng and Bai Xianyong, addressing themes such as poetic aesthetics, tragic beauty, female perspectives, and cultural symbolism. The chapters delve into multifaceted interpretations, connecting literature with cultural, philosophical, and artistic heritage. Designed for both specialists and general readers, this book enriches understanding of one of the world’s literary treasures, blending cultural appreciation with critical scholarship. It highlights the novel’s timeless narrative, intricate character portrayals, social critique, and artistic sophistication, offering a gateway to understanding Chinese culture’s enduring legacy and its global significance. Readers will discover rich analyses, compelling arguments, and fresh perspectives that deepen their appreciation for this unparalleled literary classic. The Shanghai Library, established in 1952, ranks second only to the National Library of China in scale. This book is edited based on a series of lectures on A Dream of the Red Chamber held by the Shanghai Library given by renowned scholars in the field. Wang Meng, a celebrated Chinese writer and scholar, is Honorary Chairman of the Chinese Writers’Association and former Minister of Culture. Author of nearly 100 novels, his works reflect the resilience of the Chinese people. Wang has received prestigious international honors, including Italy’s Mondello Literary Prize and honorary doctorates from multiple universities. Bai Xianyong, a renowned novelist, essayist, critic, and playwright, is Bowen Chair Professor at The Chinese University of Hong Kong and Honorary Director of its Kunqu Studies Promotion Program. Recognized for his literary excellence, he received the Lifetime Achievement Award of Shanghai Magnolia Theatre Performing Arts and the Yu Dafu Prize for Fiction.